A critical survey of the Qur’ānic qul verses and their literary function in selected polemical exchanges - Ashraf, S (2018)
For what is often described as ‘the most common command in the Qur’ān’, the literary function of the word qul (meaning ‘Say!’, in the second person singular imperative form) still remains unclear and continues to pose ‘one of the most vexed questions of Qur’ānic rhetoric’. According to the standard concordance to the Qur’ān, the word qul appears 332 times in fifty-seven of its 114 sūras. Scholars have put forward a variety of classifications and interpretations for its Qur’ānic usage. This thesis explores existing interpretations of the word qul and I then analyse and classify all 332 qul statements according to their function in the respective passages in which they occur. I posit that the vast majority (93%) of the qul statements are related to an antecedent in the Qur’ān. In many instances, these qul statements form one part in a complex matrix of responses to an antecedent, and the rhetorical effect of a qul statement in a given passage is determined by the antecedent, other responses and the syntagmatic interplay between them. This thesis demonstrates that the function of the word qul varies depending on the theme and the antecedent to which it is related. For example, quls in the form of rhetorical questions mostly draw attention to an aspect of God’s power, and they usually form a question and affirmation exchange; also nearly half of the quls in the Qur’ān respond to an audience question or statement beginning with an introductory verb derived from the Arabic letters q/w/l, such as, ‘They say (yaqūlūna), “…”’. Documenting the qul statements highlights the Qur’ān’s pervasive engagement with an audience, as well as its disputational character. Unlocking the function of qul statements reveals how Qur’ānic polemics work, and in turn how the Qur’ān engages with its audience. In the final chapter of this thesis, selected passages are examined in detail to demonstrate how the word qul in some selected passages strings together statements, objections, questions, and arguments.